Inhibition kinetics during the oxidation of binary mixtures of phenol with catechol, resorcinol and hydroquinone by phenol acclimated activated sludge - Lobo, Cintia Cecilia (2016)
In this work the aerobic degradation of phenol (PH), catechol (CA), resorcinol (RE), hydroquinone (HY) and of the binary mixtures PH+CA, PH+RE, PH+HY by phenol-acclimated activated sludge was studied. Single substrate experiments show a Haldane-type dependence of the respiration rate on PH, RE and HY, while CA corresponded to the Monod model. Binary substrate experiments demonstrated that the presence of a second substrate only affected the kinetics, but not the stoichiometry of the oxidation of the compounds tested. While CA inhibited the oxidation of PH, PH inhibited the oxidation of RE and HY. A mathematical model was developed to represent the aerobic biodegradation of the phenolic compounds tested. The agreement between the proposed model and the experimental data indicates that the proposed model can be useful for predicting substrate and dissolved oxygen concentrations in bioreactors treating phenolic wastewaters.